Assessment and Comparison of Glaucoma Knowledge Between a Group of Patients with and without Glaucoma Diagnosis - Pedro Henrique Ogata Kodama; Rodrigo Toledo Mota; Deborah dos Santos Musich; Arthur Gustavo Fernandes; Mariana Gameiro Ierardi; Leonardo Amarante Pereira; Glaucia Luciano da Veiga; Beatriz da Costa Aguiar Alves; Vagner Loduca Lima; Fernando Luiz Affonso da Fonseca (European Scientific Journal, ESJ, 2025)
Background: Glaucoma is a chronic, irreversible optic nerve neuropathy characterized by loss of visual field, which can evolve to blindness if not treated properly. This study aims to assess the level of knowledge about glaucoma between a group of diagnosed patients and a healthy group. Methods: 50 glaucoma patients (group A) of Ophthalmology service of Centro Universitário FMABC were required to answer a validated questionnaire. 50 patients without diagnosed glaucoma (Group B), answered the same questionnaire. Sociodemographic data were recorded, a source of information on the disease of 50 patients in Group A and 65 in Group B and, in group A, it was also asked for how long they have been diagnosed. Results: In the glaucoma group, 52% were female and 48% were male. In the healthy group, 66% were women and 34% were men. The mean age of group A was 66.4 years and that of group B was 55.7 years. All glaucoma patients reported knowing the disease, while 23% of Group B were unaware of the disease. 54% of Group A patients did not know that vision loss in glaucoma is slow and 46% of them reported that the disease is mostly painful. The mean score of the questions in Group A and Group B was 12.08 and 10.66, respectively (p=0.0098). Conclusion: Patients with glaucoma know more about the disease than patients without glaucoma but seem unaware of the aggravations of this disease. This study suggests the need to improve the population's knowledge about the disease and the prevention of blindness.